Prescriber compliance to direct oral anticoagulant labels and impact on outcomes in Thailand - Phannita Wattanaruengchai (2022)
Aims: This study aimed to evaluate the prescriber compliance to the approved labels of direct oral anticoagulants (DOACs) and impact of appropriateness of dosing on clinical outcomes. Methods: A retrospective study was conducted using simple-stratified random sampling of adult patients receiving ≥6 months of DOACs for various indications during 2013–2017 in 10 tertiary care hospitals. Patients were classified into 3 dosing groups including approved dose, underdosing and overdosing based on the Thai Food and Drug Administration-approved labels. Cox proportional hazard models were used to evaluate the impact of different dosings on thromboembolic and bleeding events. Results: From 1200 patients included in the data analysis, prescribing of DOACs was consistent with the approved indications in 1130 cases (94.2%) while 70 patients (5.8%) received DOACs despite having contraindications or with off-label usage. Among 1026 cases of dosing evaluation cohort, 688 patients (67.1%) received approved doses. There were 227 (21.9%) and 110 (10.7%) cases of underdosing and overdosing, respectively. Multivariate analysis showed that underdosing was associated with an increased risk of thromboembolism 3.023 (95% confidence interval [CI]: 1.291–7.080; P =.011) while overdosing was associated with an increased risk of bleeding requiring hospitalization (adjusted hazard ratio, 3.045; 95% CI, 1.501–6.178; P =.002) and Bleeding Academic Research Consortium type 2 or more (adjusted hazard ratio, 2.196; 95% CI, 1.083–4.452; P =.029). Conclusion: Prescribers’ compliance to approved indications were high. However, 1/3 of DOAC prescriptions were inconsistent with approved dosing. Dosing deviation was associated with an increase in adverse clinical outcomes.